IMPLEMENTATION OF INCLUSIVE LEARNING STRATEGIES IN INTERVENING READING DIFFICULTIES IN DYSLEXIC STUDENTS - Ahmad Zulkifli Lubis; Devi Sulaeman; Mia Audina Musyadad; Ahmad Riyadi; Diah Widiawati; Asep Supriatna Asep (JCI Publisher, 2026)
Reading skills are the primary foundation for successful learning in elementary education, but not all students have optimally developed literacy skills, including students with dyslexia. This situation demands the implementation of adaptive and responsive inclusive learning strategies in regular classrooms. This study aims to analyze and describe the implementation of inclusive learning strategies in interventions for reading difficulties in dyslexic students at State Islamic Elementary School (MIN) 1 Karawang. The study used a qualitative approach with a case study approach. Data were collected through observation, in-depth interviews, and documentation studies. Data were then analyzed using an interactive model that included data reduction, data presentation, and conclusion drawing. The results showed that strategy implementation was carried out through adaptive planning, differentiated learning, and individual development-based evaluation integrated into regular learning. Teachers modified materials, used visual media, segmented text, and continuously monitored student progress. The implications of this research emphasize the importance of strengthening teachers' pedagogical competencies in designing inclusive literacy interventions and the need for institutional support to ensure the sustainability of adaptive learning practices in madrasas.